Molecular dynamics simulation on glass transition temperature of isomeric polyimide (eXPRESS Polymer Letters)
It is an abnormal phenomenon that glass transition temperature (Tg) of isomeric polyimide (PI) is higher than its corresponding symmetrical PI. To illustrate this phenomenon at the molecular scale, we applied molecular dynamics method to predict the Tg of PI, which were prepared based on 4,4’-oxydianiline (ODA) and 3,3’,4,4’-biphenyltetracarboxylic dianhydride (3,3’,4,4’-BPDA), and its isomeric system (2,2’,3,3’-BPDA-ODA). Simulation result is consistent with experimental value. Non-bond energy plays an important role in glass transition process, for it has an abrupt change near Tg. The higher free volume fraction of isomeric PI can provide the polymer with more space to obtain segmental motion. However, from the torsion angle distribution calculations, it is shown that the torsion angle of its biphenyl group is constrained. Furthermore, from mean square displacement and vector autocorrelation functions calculations, this group is observed to rotate against other groups in the glassy state, and increases the chain rigidity to a great extent. So the isomeric PI needs much more relaxation time for the segment motion. Therefore, the higher Tg of isomeric PI is mainly attributed to the chain rigidity for the time scale, not the free volume for the space scale.